Crystal Structure and Catalytic Mechanism of CouO, a Versatile C-Methyltransferase from Streptomyces rishiriensis. - Tea Pavkov-Keller; Kerstin Steiner; Mario Faber; Martin Tengg; Helmut Schwab; Mandana Gruber-Khadjawi; Karl Gruber (PLoS ONE)
Friedel-Crafts alkylation of aromatic systems is a classic reaction in organic chemistry, for which regiospecific mono-alkylation, however, is generally difficult to achieve. In nature, methyltransferases catalyze the addition of methyl groups to a wide range of biomolecules thereby modulating the physico-chemical properties of these compounds. Specifically, S-adenosyl-L-methionine dependent C-methyltransferases possess a high potential to serve as biocatalysts in environmentally benign organic syntheses. Here, we report on the high resolution crystal structure of CouO, a C-methyltransferase from Streptomyces rishiriensis involved in the biosynthesis of the antibiotic coumermycin A1. Through molecular docking calculations, site-directed mutagenesis and the comparison with homologous enzymes we identified His120 and Arg121 as key functional residues for the enzymatic activity of this group of C-methyltransferases. The elucidation of the atomic structure and the insight into the catalytic mechanism provide the basis for the (semi)-rational engineering of the enzyme in order to increase the substrate scope as well as to facilitate the acceptance of SAM-analogues as alternative cofactors.